2021
DOI: 10.1680/jmacr.19.00050
|View full text |Cite
|
Sign up to set email alerts
|

The efficiency of confinement reinforcement in post-tensioning anchorage zones

Abstract: In this paper, a parametric study based on the load transfer test specified in ETAG 013 was performed with the aim of investigating the efficiency of the confining reinforcement in the local anchorage zone of post-tensioning tendons, in particular when there are two types of confining reinforcement, spiral and stirrups. The parametric study was conducted using the finite element software ATENA 3D and included 45 specimens of ordinary concrete reinforced with a combination of spirals and stirrups. The models we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…Besides the effect of the type of anchorage, and as observed by Marchão et al 10 and by Rebelo et al, 11 one of the causes of the observed differences could be related to the fact that in the case where there are, simultaneously, two types of confinement reinforcement, the outer reinforcement is not as effective as the inner one. Therefore, when calculating the bearing strength, the arithmetic superimposition of both spiral and stirrups in confinement can be against safety leading to higher loads.…”
Section: Authormentioning
confidence: 86%
See 2 more Smart Citations
“…Besides the effect of the type of anchorage, and as observed by Marchão et al 10 and by Rebelo et al, 11 one of the causes of the observed differences could be related to the fact that in the case where there are, simultaneously, two types of confinement reinforcement, the outer reinforcement is not as effective as the inner one. Therefore, when calculating the bearing strength, the arithmetic superimposition of both spiral and stirrups in confinement can be against safety leading to higher loads.…”
Section: Authormentioning
confidence: 86%
“…Therefore, when calculating the bearing strength, the arithmetic superimposition of both spiral and stirrups in confinement can be against safety leading to higher loads. Also, according to the same authors, 10,11 the different confinement reinforcement levels have different strains along the height of the confined zone and just some of the reinforcing bars attained yielding, contributing to the existence of non-uniform confinement forces along the height, and consequently smaller than the ones considered in the proposed equations.…”
Section: Authormentioning
confidence: 92%
See 1 more Smart Citation
“…Because Equations ( 8) and ( 17) were verified for the minimum anchorage spacing [15,16], κ is 1.0 for the minimum anchorage spacing. Next, a revised equation for the spiral-dependent contribution of lateral confinement to the bearing strength was presented as Equation (21). The exponent of Equation ( 20) was determined to create κ in Equation ( 21), which is identical to the average increase (1.12 = 1.144+1.093 2 ) from A core for the minimum anchorage spacing.…”
Section: Calibration Of the Design Equationmentioning
confidence: 99%
“…Mao et al [17] and Lee and Kim [18] focused on stress distribution, crack formation, and ultimate capacity with respect to the bursting force in the anchorage zone. Bonetti et al [19], Marchão et al [20], Rebelo et al [21] performed on the influence of confining reinforcement on the bearing strength of concrete blocks. Their research took similar approaches as other research, such as the investigation of the existing and proposed design equations for better estimation.…”
Section: Introductionmentioning
confidence: 99%